Comparative Physiological and Proteomic Analysis Reveal Distinct Regulation of Peach Skin Quality Traits by Altitude - Karagiannis, Evangelos; Tanou, Georgia; Samiotaki, Martina; Michailidis, Michail; Diamantidis, Grigorios; Minas, Ioannis S.; Molassiotis, Athanassios (Frontiers in Plant Science, 2016)
The role of environment in fruit physiology has been established; however, knowledge regarding the effect of altitude in fruit quality traits is still lacking. Here, skin tissue quality characters were analysed in peach fruit (cv. June Gold), harvested in 16 orchards located in low (71.5 m mean) or high (495. m mean) altitutes sites. Data indicated that soluble solids concentration and fruit firmness at commercial harvest stage were unaffected by alitute. Peach grown at high-altitude environment displayed higher levels of pigmentation and specific antioxidant-related activity in their skin at the commercial harvest stage. Skin extracts from distinct developmental stages and growing altitudes exhibited different antioxidant ability against DNA strand-scission. The effects of altitude on skin tissue were further studied using a proteomic approach. Protein expression analysis of the mature fruits depicted altered expression of 42 proteins that are mainly involved in the metabolic pathways of defense, primary metabolism, destination/storage and energy. The majority of these proteins were up-regulated at the low-altitude region. High-altitude environment increased the accumulation of several proteins, including chaperone ClpC, chaperone ClpB, pyruvate dehydrogenase E1, TCP domain class transcription factor and lipoxygenase. We also discuss the altitude-affected protein variations, taking into account their potential role in peach ripening process. This study provides the first characterization of the peach skin proteome and helps to improve our understanding of peach’s response to altitude.